Variation of the electronic functionality of self-seeded germanium nanowires through synthesis determined core-shell interface states - Connaughton, Stephen (Trinity College (Dublin, Ireland). School of Physics, 2015)
Bottom up grown germanium nanowires may have an important role to play in future electronic devices. While the electrical properties of nanowires grown using a metallic seed as a catalyst have been extensively reported we study self-seeded nanowires in this thesis. Such wires are core-shell in nature and are grown without any intentional doping. Self-seeded nanowires have been previously proposed as an attractive alternative to conventionally grown wires due the alleviation of complications arising from unintentional doping from the metallic seed.
PUBLISHED
Keywords: Physics; Ph.D. Trinity College Dublin; Physics, Ph.D.